The Review of Beamforming Technology Based on Optical True Time Delay Line - Shiyi XIA; Guotong LI (天地一体化信息网络)
The important role satellite communications plays in next-generation communication protocols brings both opportunities and challenges.Beamforming is an essential technology for effi cient and fl exible utilization of onboard resources.To explored a better beamforming technology, the optical control beamforming composed of the optical real-time delay line and the traditional analog beam were compared in principle.The phased array beamforming technology based on optical true time delay line meets the expectations of small size, lightweight, and low power in satellite communication.Phased arrays based on optical true delay lines could easily achieved no squint during beam scanning.The technical advantages and constraints of beamforming of optical real-time delay lines under diff erent technical paths were analyzed.For example, based on micro-ring resonator arrays, based on grating delay lines, based on multi-path switching and optical switches, and based on wavelength-selective optical true time delay lines.Finally, the research status of the existing optical beamforming technology was summarized.The possibility of realization in satellite interconnection was proposed, and its future development direction was predicted.